(3fRgI GdbdhH aj JaSjQ ZQjH GdbQBfs - (3CHh HcQ eMeO Hf YRjR GdSLSJGfjs ((3eSYhO Hf CMeO Hf eSYhO Hf MeRI GdWdjei s)
(3ChdgG (B:s
(3gPG cJGH JaSjQ ZQjH GdbQBf Cda Ydi MQha GdeYLe djbQH JfGhdg hjSgd JMaXg Ydi ef CQGOg GdgeRI GdeaJhMI Cde hSGFQ MQha GdgLGA ai ChGFd GdShQ s
(3BNQgG (B:s
(3jhbVhf jSQYhf HGdjGA GdecShQI bjd djS ai GdYQHjI cdeI ChdgG jGA ecShQI ZdG bhdge jSGQ hjSGQ ddjO Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HChdgG hba dLGeY UfYGA HCeQ CejQ GdeDefjf GdeJhcd Ydi Gddg SfI (B1343 (3g`s
(3eQJH Ydi MQha GdeYLes
(3cJHJ HNW eged GdfbW CMjGfkGs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdJGQjNs